2008
DOI: 10.1111/j.1752-0606.2008.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Intimate Partner Violence Universal Screening by Family Therapy Interns: Implications for Practice, Research, Training, and Supervision

Abstract: Although a few family therapy researchers and clinicians have urged universal screening for intimate partner violence (IPV), how screening is implemented-and, in particular, client and therapist response to screening-is vaguely defined and largely untested. This qualitative study examined the dilemmas experienced by couples and family therapy interns when implementing universal screening for IPV in an outpatient clinic setting. Twenty-two graduate students in a COAMFTE-accredited program were interviewed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Bograd and Mederos (1999) found that even in a therapeutic situation, most couples do not disclose violence unless asked specifically about it. Additionally, most therapists only talk about violence with a couple who is presenting for issues of violence, and therapists vary widely in their screening processes of violent couples (Todahl, Linville, Chou, & Maher-Cosenza, 2008). However, research shows that 53% of couples in therapy have been violent at one time or another, suggesting that therapists in general need to be more assertive when assessing for violence (O'Leary, Vivian, & Malone, 1992).…”
Section: Traditional Violence Treatmentsmentioning
confidence: 99%
“…Bograd and Mederos (1999) found that even in a therapeutic situation, most couples do not disclose violence unless asked specifically about it. Additionally, most therapists only talk about violence with a couple who is presenting for issues of violence, and therapists vary widely in their screening processes of violent couples (Todahl, Linville, Chou, & Maher-Cosenza, 2008). However, research shows that 53% of couples in therapy have been violent at one time or another, suggesting that therapists in general need to be more assertive when assessing for violence (O'Leary, Vivian, & Malone, 1992).…”
Section: Traditional Violence Treatmentsmentioning
confidence: 99%
“…As depicted in the previous scenario, behavior may appear "mild" by conventional definitions and may not register for clients or therapists as IPV, though "mild" behavior can have severely negative consequences for individuals and interpersonal relationships. Failure to recognize "mild" violence and failure to carefully assess its impact can organize therapists to inadvertently deny and minimize the existence of and consequences of very common forms of IPV (Bograd & Mederos, 1999;Todahl, Linville, Chou, & Maher-Cosenza, 2008). As described by Jory (2004), "clinicians should never collude with minimization or denial by failing to address acts, such as slapping or pushing, directly as abuse" (p. 29).…”
mentioning
confidence: 95%
“…Given the prevalence of IPV, its negative social and health impact, and its pertinence in clinical work (Centers for Disease Control and Prevention, 2008), several researchers have argued that family therapists and other healthcare providers should routinely screen for IPV (Bograd & Mederos, 1999;Stith et al, 2003;Todahl et al, 2008). However, researchers have not yet adequately investigated whether IPV universal screening improves treatment outcomes (Nelson, Nygren, McInerney, & Klein, 2004;Ramsay, Richardson, Carter, Davidson, & Feder, 2002;Wathen & MacMilan, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Although the IPV-SAT has been practiced at a university-based training clinic for approximately 5 years without known moderate or severe adverse effects, the IPV-SAT procedure has been studied only from the vantage point of practitioners-in-training and supervisors (Todahl et al, 2008). A random selection of 100 clients who were given the four IPV-SAT questions at the Center for Family Therapy (CFT) 5 responded in writing to 99% (396/400) of the items at the time of intake.…”
Section: Discussionmentioning
confidence: 99%